Synthesis and characterization of some complexes of Co(II), Ni(II), Cu(II),Zn(II),Cd(II) and Hg(II) with Schiff–base( N-benzylidine furan -3-Carbohydrazide ) - Janan Idress Mohammed Shaheen (Al-Qadisiyah Journal of Pure Science, 2019)
A new complexes of general formula [M(R)2] (NO3)2] where M= Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II), are synthesized by the coordination of these metal salts with Schiff-base [N-benzylidine furan-3-carbohydrazides (RH)].The Schiff base is prepared by condensation of   Furan -3-carbohydrazide and 2-hydroxy benzaldehyde (1 : 1 molar ratio). These complexes are characterized by their  IR , UV/ Vis spectra and molar conductivity measurements. These results indicate that the ligands  (RH) are coordinated with all metals as didentate via the most active sites , imine nitrogen (azomethane ), phenolic oxygen in addition to carbonyl oxygen .